Motion of vortices in ferromagnetic spin-1 BEC: Современные проблемы нелинейной физики магнетизма. II. Топологические солитоны - Sonin, E.B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The paper investigates dynamics of nonsingular vortices in a ferromagnetic spin-1 BEC, where spin and mass superfluidity coexist in the presence of uniaxial anisotropy (linear and quadratic Zeeman effect). The analysis is based on hydrodynamics following from the Gross–Pitaevskii theory. Cores of nonsingular vortices are skyrmions with charge, which is tuned by uniaxial anisotropy and can have any fractal value between 0 and 1. There are circulations of mass and spin currents around these vortices. The results are compared with the equation of vortex motion derived earlier in the Landau–Lifshitz–Gilbert theory for magnetic vortices in easy-plane ferromagnetic insulators. In the both cases the transverse gyrotropic force (analog of the Magnus force in super-fluid and classical hydrodynamics) is proportional to the charge of skyrmions in vortex cores.